Effects of aquaculture fallowing on the recovery of macrofauna communities. Issue 1 (15th August 2015) - Zhulay, Irina; Reiss, Katrin; Reiss, Henning
Highlights: We studied temporal and spatial effects of aquaculture fallowing on benthos. Highly opportunistic species and low diversity characterised the fish farm stations. After 2 months fallowing only a decline in few opportunistic species was found. After 6 months fallowing the macrofauna partly recovered. Seasonal timing of fallowing may affect the recovery dynamics. Abstract: The fallowing period is a management measure in aquaculture where the production is paused for a few months to reduce the impact on the benthic environment. We studied the effects of different fallowing periods on the recovery of macrofauna at two salmon farms in Norway. The macrofauna at the farm stations were characterised by high abundances of opportunistic taxa (e.g. Capitella spp.), low diversity and significantly different community structure compared to reference sites. The fallowing initiated macrofauna recovery at both farm stations, indicated by a decline of dominant opportunistic taxa after 2 months. Significant changes in taxa composition occurred only after 6 months, although indications of disturbance were still evident. Surprisingly, no corresponding spatial or temporal differences were found in the sediment parameters such as redox, TOC and pH. The results suggest that macrofauna is a more sensitive indicator and that the seasonal timing of fallowing may affect recovery dynamics.